(untitled) (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2026)
Social welfare programs play a crucial role in supporting vulnerable populations by providing financial assistance, healthcare access, housing support, and other essential services. However, traditional welfare management systems often face challenges such as manual case processing, fragmented data sources, delayed decision-making, and inefficient resource allocation. These limitations can lead to delays in service delivery, increased administrative burden, and reduced effectiveness of welfare programs. Recent advancements in artificial intelligence, particularly Agentic AI, offer new opportunities to modernize social welfare systems. Agentic AI refers to autonomous AI systems capable of reasoning, decision-making, and executing tasks with minimal human intervention. By integrating intelligent agents into social welfare platforms, governments and organizations can automate case management processes, analyze large-scale socio-economic data, and dynamically allocate resources to individuals and communities based on real-time needs. This article explores the architecture and operational framework of autonomous social welfare systems powered by Agentic AI. The proposed approach combines multi-agent systems, machine learning models, and cloud-based data infrastructure to enable intelligent case assessment, eligibility verification, predictive risk analysis, and automated service recommendations. The framework also emphasizes transparency, accountability, and ethical considerations to ensure fairness and privacy protection in automated decision-making. Furthermore, the study discusses potential system components such as data ingestion pipelines, AI-driven decision engines, citizen interaction interfaces, and policy compliance modules. Conceptual diagrams and tables illustrate how agent-based workflows can improve efficiency, reduce operational costs, and enhance service delivery across large-scale public welfare programs. The findings suggest that integrating Agentic AI into social welfare management can significantly improve responsiveness, accuracy, and scalability of welfare services. By enabling autonomous coordination between data systems, policy rules, and service providers, intelligent welfare platforms can support governments in delivering timely assistance while ensuring optimal use of public resources.